1997
DOI: 10.1128/iai.65.12.5301-5308.1997
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Chlamydia trachomatis alters the tyrosine phosphorylation and/or localization of several host cell proteins including cortactin

Abstract: Infection of epithelial cells by two biovars of Chlamydia trachomatis results in the tyrosine phosphorylation of several host proteins. The most prominent change in host protein tyrosine phosphorylation involves a complex of proteins with molecular masses of 75 to 85 kDa (pp75/85) and 100 kDa (pp100). The C. trachomatisinduced tyrosine phosphorylation of pp75/85 and pp100 is observed in several cell lines, including epithelial cells, fibroblasts, and macrophages. Subcellular fractionation and detergent solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…Furthermore, our results demonstrate that viable C. pneumoniae is not required for HUVEC stimulation, suggesting that cell surface binding and/or phagosomal entry events are important in transducing the signals involved in upregulating cytokine or chemokine gene expression in the HUVEC. Such early events capable of inducing host cell signal transduction pathways via host protein tyrosine phosphorylation have been described for C. trachomatis (4,5) and are activated also by heat-or UV-treated C. trachomatis. A common signal transduction pathway may be activated in C. pneumoniae-infected HUVEC.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, our results demonstrate that viable C. pneumoniae is not required for HUVEC stimulation, suggesting that cell surface binding and/or phagosomal entry events are important in transducing the signals involved in upregulating cytokine or chemokine gene expression in the HUVEC. Such early events capable of inducing host cell signal transduction pathways via host protein tyrosine phosphorylation have been described for C. trachomatis (4,5) and are activated also by heat-or UV-treated C. trachomatis. A common signal transduction pathway may be activated in C. pneumoniae-infected HUVEC.…”
Section: Discussionmentioning
confidence: 93%
“…C. trachomatis infection as well as infection due to other bacteria leads to the production of cytokines and inflammatory mediators that also cause increase in CFTR expression and activity as reviewed by Ajonuma et al (2002) and subsequent fluid formation as demonstrated in this study by IL-1b. Secondly, C. trachomatis infection is known to induce protein tyrosine phosphorylation even as early as 15 min (Bliska et al, 1993;Birkelund et al, 1994;Fawaz et al, 1997;Hosseinzadeh et al, 2000) and upregulation (Xia et al, 2003) of several proteins. Interestingly, in this study, C. trachomatis infection also increased the expression of CFTR.…”
Section: Resultsmentioning
confidence: 99%
“…The identity of the 80 and 82 kDa proteins that are phosphorylated in response to C. albicans remains to be determined. Known tyrosine kinase substrates with similar molecular masses include, cortactin, the 85 kDa regulatory subunit of class IA phosphatidylinositide 3-kinase, and the ezrin, radixin and moesin family of proteins (Takeuchi et al, 1994;Dehio et al, 1995;Fawaz et al, 1997;Lowry et al, 1998;Wymann and Pirola, 1998;Skoudy et al, 1999). Experiments are in progress to determine whether any of these candidate proteins are phosphorylated in endothelial cells that are infected with C. albicans.…”
Section: Discussionmentioning
confidence: 99%